(untitled) (Bangladesh Journal of Medical Science, 2019)
Background: Birth defect is one of the most important causes of neonatal mortality worldwide. In a developing country like Bangladesh many possible factors for birth defects are present which should be identified. This study was performed to determine those risk factors of birth defect and complications associated with it. Materials and Methods: A hospital based matched case-control study was conducted from August 2015 to July 2016 in department of Neonatology along with Obstetrics and Gynecology at BSMMU. A total of 98 mother-infant pair (49 babies with birth defect as cases and 49 healthy babies without any birth defects as controls) was included in the study. For each case, a gestational age, sex and post-natal age matched control was taken. Data was collected by face to face interview. Univariate and multivariate conditional logistic regression models were computed to examine the effect of independent variables on outcome variable using SPSS 23.0. Variables with p-value <0.05 were considered statistically significant. Results: The mean (± SD) birth weight for cases and controls were 2718.37 (±756.9) grams, and 2617.14 (±978.8) grams respectively. Cardiovascular system was the predominant system (21%) involved in birth defects. Maternal age between 20-29 years (AOR: 4.69; 95% CI 1.078, 20.448), less than four antenatal care visits (AOR: 10.07; 95% CI 2.816, 36.0), no multivitamin intake (AOR: 7.38; 95% CI 1.791, 30.365) and presence of maternal diabetes (AOR: 0.194; 95% CI 0.047, 0.799) were significantly associated with birth defects among newborns. Sepsis, asphyxia, hypoglycemia and dyselectrolytemia were the most prevalent problems among these babies. The need of intravenous fluid, thermal care, antibiotics and mechanical ventilation was also high among the cases. Conclusion: Birth defect is an upcoming issue in current newborn health situation which need to be prioritized. Significant risk factors should be addressed timely for early diagnosis and proper management of these babies can help in reduction of mortality. Bangladesh Journal of Medical Science Vol.19(1) 2020 p.133-140